Mother’s rights to life, a medical approach to abortion - H Shamshiri-Milani (JRI, 2005)
Abortion is the termination of pregnancy either spontaneously or intentionally before fetus develops sufficiently to survive outside its mother’s womb. Not all zygotes, which are the result of spermatozoid and ovum fertilization, will reach implantation stages and too many pregnancies terminate inevitably because of fetal or maternal causes. The data on maternal mortality rate and complications which unwanted pregnancies face and the number of attempts for induced abortions is considerable. Although, at the first glance, it seems that abortion is a medical issue, but diverse fields have their statements according to their approaches. These statements are often expertised, judgmental and incisive but most of them are theoretical dis-cussions and cover different beneficiaries and the mothers’ decisions, rights and health for the continuation or termination of pregnancy may be of the least concern. Even in the cases of the mothers’ or fetuses’ illnesses, the decision on maintaining the health of pregnant mothers de-pends on other dimensions of interest. This article, without agreeing or disagreeing with abor-tion, provides information on pregnancy and abortion, and the reader is left free for the analysis and decision making.
Keywords: Pregnancy, Abortion, Mothers health, Rights, Unwanted pregnancy